The most commonly available woody plant species are the most useful for human populations: a meta-analysis - Gonçalves, Paulo Henrique Santos; Albuquerque, Ulysses Paulino; de Medeiros, Patrícia Muniz (Ecological applications, 2016)
An increasing number of studies have aimed to clarify the factors leading human groups to prioritize the use of some woody plant species compared to others. Some of these studies have tested the apparency hypothesis in aiming to understand this phenomenon. According to the apparency hypothesis, the most commonly available local plant species on a forest path are the most useful to that local human population. However, the sparse and diverse nature of the results from studies investigating the factors that influence human exploitation of plant resources motivated us to perform a meta-analysis on the apparency hypothesis. We searched in the main databases (Scopus, ScienceDirect, Google Scholar, and Scielo) for studies that correlated the environmental availability of woody species (estimated through vegetation parameters) with the degree of importance of such species to the local human population (estimated by means of the use value index). Overall, this meta-analysis supported the apparency hypothesis, although we also found high levels of heterogeneity in these studies. When the distinct uses of woody flora were considered separately, we found that local species availability is important for fuelwood (firewood and charcoal) and construction (houses, fences, etc.) purposes but does not explain medicinal and technological (object manufacture) plant use. We found no important differences in correlation values between the degree of species importance for people and the different vegetation parameters, although correlations are slightly higher for the dominance and importance value index. Our findings suggest that the exploitation of woody flora is influenced by local availability.